2014
DOI: 10.1242/dev.091538
|View full text |Cite
|
Sign up to set email alerts
|

How to make a cardiomyocyte

Abstract: During development, cardiogenesis is orchestrated by a family of heart progenitors that build distinct regions of the heart. Each region contains diverse cell types that assemble to form the complex structures of the individual cardiac compartments. Cardiomyocytes are the main cell type found in the heart and ensure contraction of the chambers and efficient blood flow throughout the body. Injury to the cardiac muscle often leads to heart failure due to the loss of a large number of cardiomyocytes and its limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
129
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 204 publications
(214 reference statements)
1
129
0
3
Order By: Relevance
“…Thus, methods to generate induced cardiac-like myocytes (iCMs) by reprogramming fibroblasts with combinations of cardiac transcription factors represent a potential approach for enhancing cardiac repair (2)(3)(4)(5)(6)(7)(8). Various mixtures of proteins, microRNAs, and small molecules have been shown to activate cardiac gene expression in fibroblasts (9), confirming original observations made merely 5 y ago (2).…”
mentioning
confidence: 57%
“…Thus, methods to generate induced cardiac-like myocytes (iCMs) by reprogramming fibroblasts with combinations of cardiac transcription factors represent a potential approach for enhancing cardiac repair (2)(3)(4)(5)(6)(7)(8). Various mixtures of proteins, microRNAs, and small molecules have been shown to activate cardiac gene expression in fibroblasts (9), confirming original observations made merely 5 y ago (2).…”
mentioning
confidence: 57%
“…Paraxial mesoderm subsequently buds off into tissue segments known as somites 4 , with dorsal somites (dermomyotome) giving rise to brown fat, skeletal muscle, and dorsal dermis, and ventral somites (sclerotome) yielding the bone and cartilage of the spine and ribs 5 . Separately, lateral mesoderm goes on to form limb bud mesoderm 6 and cardiac mesoderm 7 , the latter of which generates cardiomyocytes and other heart constituents.…”
Section: Background and Summarymentioning
confidence: 99%
“…The differentiation of multi-potent mesodermal cells to a cardiac fate is orchestrated by various signaling events and the cardiac transcriptional program (for review see [3234]). In this study we showed that Tbx20 is a critical component of the cardiac transcriptional program that drives the formation of cardiac progenitor cells.…”
Section: Discussionmentioning
confidence: 99%